2003
DOI: 10.1002/art.11040
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 prevents nitric oxide–induced apoptosis in articular chondrocytes

Abstract: Objective. To deliver and overexpress the hsp70 gene in cultured chondrocytes to investigate its effect on nitric oxide (NO)-induced apoptosis of chondrocytes.Methods. Primary chondrocyte cultures were established from rabbit joints. The cells were transduced with an empty adenovirus vector (Ax1w) or an adenovirus vector harboring the hsp70 E-tag fusion gene (AxSHEwt Degradation of articular cartilage, the major component of a joint, causes serious dysfunction of joints. Osteoarthritis (OA) is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…In cells that express Hsp70, however, Hsp70 expression has been shown to exert a strongly anti-apoptotic effect (Terauchi et al 2003;Saleh et al 2000). In this study, we used three different types of assessments to show that apoptosis is significantly increased: the changes in mitochondrial membrane potential that occur at an early stage of apoptosis; activity of caspase-3, an enzyme in the caspase family that is activated downstream; and DNA fragmentation, the final stage of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In cells that express Hsp70, however, Hsp70 expression has been shown to exert a strongly anti-apoptotic effect (Terauchi et al 2003;Saleh et al 2000). In this study, we used three different types of assessments to show that apoptosis is significantly increased: the changes in mitochondrial membrane potential that occur at an early stage of apoptosis; activity of caspase-3, an enzyme in the caspase family that is activated downstream; and DNA fragmentation, the final stage of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The chondrocytes, isolated from the knee joints of rabbits, were seeded to the 96-well plates at 2 9 10 4 cells per well and stabilized for 24 h. After incubation with SFC (30, 100, 300 and 1,000 lg/ml) plus SNP (2 mM), the cells were fixed with methanol acetic acid for 10 min followed by staining with Hoechst 33258 1 mg/ml for 5 min at room temperature. The cells were then washed twice with PBS, observed and immediately photographed under a fluorescence microscope with excitation at 355 nm and emission at 465 nm (Terauchi et al 2003). …”
Section: Hoechst 33258 Stainingmentioning
confidence: 99%
“…It has been reported that HSP70 expression levels in chondrocytes are correlated with histological severity in OA, 8,9 and that the overexpression of HSP70 results in promotion of metabolic activity of chondrocytes 10 and protection of chondrocytes from various stresses. 11,12 In chondrocytes of OA patients, however, the expression level of HSP70 may not be high enough to eliminate stress-induced damages of the cartilage or accelerate metabolic activity in the damaged cartilage; this may cause the progression of the disorder. Control of HSP70 expression in the articular cartilage by thermotherapy may provide a novel therapeutic strategy for OA.…”
Section: Introductionmentioning
confidence: 99%